2020
DOI: 10.1021/acsomega.0c03000
|View full text |Cite
|
Sign up to set email alerts
|

Why Can Cationic Halogen Bond Donors Activate the Ritter-Type Solvolysis of Benzhydryl Bromide but Cationic Hydrogen Bond Donors Can Not?

Abstract: It is found by experiment that the cationic halogen bond donors (cationic iodoimidazolium compounds) can activate the Ritter-type solvolysis of benzhydryl bromide, while the cationic hydrogen bond donors (cationic imidazolium compounds) could not. To understand the activation mechanism, various noncovalent interactions between benzhydryl bromide and a series of activators in solution, including halogen bond, hydrogen bond, lone pair···π/π + , and C–H···π/π + , were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The dehydration reaction is believed to be initiated by the activation of the hydroxy group (−OH) associated to C2 of fructose (C 2 -OH) through the hydrogen-bond interaction between the −OH group and positively charged pyridinium head group and the negatively charged sulfonate group (−SO 3 – ), as shown in Scheme . Then, with the elimination of the hydroxide ion (OH – ), the positively charged active transitional ion was formed, which can be stabilized by the negatively charged sulfonate group. , After removal of the proton (H + ) from the positively charged transitional intermediate, the active intermediate 1* was formed and stabilized/activated by the inner salt through the hydrogen-bond interaction. , The intermediate 1* can be isomerized subsequently into the more stable intermediate 1 that can be further catalyzed by dehydration through successive elimination of OH – and H + to form the target HMF. Hence, the electrophilicity of the positively charged pyridinium -based cationic moiety and the electronegativity of the −SO 3 – anionic moiety played the dual roles in the activation of substrates by a relay of cooperative hydrogen-bond and charge–charge interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dehydration reaction is believed to be initiated by the activation of the hydroxy group (−OH) associated to C2 of fructose (C 2 -OH) through the hydrogen-bond interaction between the −OH group and positively charged pyridinium head group and the negatively charged sulfonate group (−SO 3 – ), as shown in Scheme . Then, with the elimination of the hydroxide ion (OH – ), the positively charged active transitional ion was formed, which can be stabilized by the negatively charged sulfonate group. , After removal of the proton (H + ) from the positively charged transitional intermediate, the active intermediate 1* was formed and stabilized/activated by the inner salt through the hydrogen-bond interaction. , The intermediate 1* can be isomerized subsequently into the more stable intermediate 1 that can be further catalyzed by dehydration through successive elimination of OH – and H + to form the target HMF. Hence, the electrophilicity of the positively charged pyridinium -based cationic moiety and the electronegativity of the −SO 3 – anionic moiety played the dual roles in the activation of substrates by a relay of cooperative hydrogen-bond and charge–charge interactions.…”
Section: Resultsmentioning
confidence: 99%
“… 62 64 Then, with the elimination of the hydroxide ion (OH – ), the positively charged active transitional ion was formed, which can be stabilized by the negatively charged sulfonate group. 64 , 65 After removal of the proton (H + ) from the positively charged transitional intermediate, the active intermediate 1* was formed and stabilized/activated by the inner salt through the hydrogen-bond interaction. 64 , 66 The intermediate 1* can be isomerized subsequently into the more stable intermediate 1 that can be further catalyzed by dehydration through successive elimination of OH – and H + to form the target HMF.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 In 2008, Bolm et al 6 reported the Hantzsch ester reduction of 2-phenylquinoline activated by halogen bonds, which is the application of halogen bonds in catalytic reactions. In the following years, halogen bond donors have been used as catalysts in different reactions by activating various functional groups, such as amides, 7,8 carbonyl groups, [9][10][11] halides, [12][13][14] nitro groups, 15 and imines. 16,17 In these reactions, halogen bond donor catalysts are mainly used to activate substrates containing lone pair-possessing heteroatoms to complete the catalytic reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The π electrons in aromatic rings and the p orbital electrons in halogens form a conjugated system, making the halogenated organic compounds extremely stable. 14 pollutants discharged into the ecosystem could easily accumulate, giving rise to significant environmental concerns. Furthermore, these pollutants have the potential to move through the food chain, leading to the accumulation of toxins that result in deformities, genetic mutations, and an increased risk of cancer.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, halogens in traditional quaternary ammonium salt-based corrosion inhibitors have strong environmental impacts. The π electrons in aromatic rings and the p orbital electrons in halogens form a conjugated system, making the halogenated organic compounds extremely stable . Undegradable halogenated organic pollutants discharged into the ecosystem could easily accumulate, giving rise to significant environmental concerns.…”
Section: Introductionmentioning
confidence: 99%